2021
DOI: 10.1136/gutjnl-2020-320937
|View full text |Cite
|
Sign up to set email alerts
|

NTPDase8 protects mice from intestinal inflammation by limiting P2Y6 receptor activation: identification of a new pathway of inflammation for the potential treatment of IBD

Abstract: ObjectiveNucleotides are danger signals that activate inflammatory responses via binding P2 receptors. The nucleoside triphosphate diphosphohydrolase-8 (NTPDase8) is an ectonucleotidase that hydrolyses P2 receptor ligands. We investigated the role of NTPDase8 in intestinal inflammation.DesignWe generated NTPDase8-deficient (Entpd8–/–) mice to define the role of NTPDase8 in the dextran sodium sulfate (DSS) colitis model. To assess inflammation, colons were collected and analysed by histopathology, reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…To verify the antiapoptotic role of ghrelin in vivo, we used ghrelin to treat the DSS-and TNBS-induced colitis models, respectively. As previously reported, the colon of mice treated with DSS or TNBS displayed more significant apoptosis (Arab et al, 2021;Salem et al, 2021) (Figures 3A, 3B). Compared with the treatment group, ghrelin reduced the colon cell apoptosis in a dose-dependent manner, and such an antiapoptotic effect of ghrelin could be reversed by [D-lys3]-GHRP-6 ( Figures 3A,B).…”
Section: Ghrelin Protects Colitis Tissues Cells From Apoptosis In Vivosupporting
confidence: 83%
“…To verify the antiapoptotic role of ghrelin in vivo, we used ghrelin to treat the DSS-and TNBS-induced colitis models, respectively. As previously reported, the colon of mice treated with DSS or TNBS displayed more significant apoptosis (Arab et al, 2021;Salem et al, 2021) (Figures 3A, 3B). Compared with the treatment group, ghrelin reduced the colon cell apoptosis in a dose-dependent manner, and such an antiapoptotic effect of ghrelin could be reversed by [D-lys3]-GHRP-6 ( Figures 3A,B).…”
Section: Ghrelin Protects Colitis Tissues Cells From Apoptosis In Vivosupporting
confidence: 83%
“…P2Y 6 R abundance has been reported to increase in experimental colitis in mice, and the inhibition of P2Y 6 R by MRS2578 or the deletion of P2Y 6 R specifically in intestinal epithelial cells improves symptoms and is protective against intestinal inflammation ( 8 , 15 ). Consistent with those reports, we found that global P2Y 6 R deletion attenuated DSS-induced colitis, supporting the involvement of P2Y 6 R in the exacerbation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Cys 220 modification of P2Y 6 R protects mice against DSS-induced colitis It has been reported that P2Y 6 R participates in IBD such as Crohn's disease and ulcerative colitis (8,15) and that dietary supplementation with natural ITCs exerts therapeutic anti-inflammatory effects (16). To determine whether modification of P2Y 6 R at Cys 220 affects intestinal inflammation in vivo, we performed experiments in whole-body P2Y 6 R knockout and P2Y 6 R (C220S) knockin mice in which colitis was induced by dextran sulfate sodium (DSS).…”
Section: Cys 220 Modification Contributes To Ligand-stimulated P2y 6 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was found that NTPDase8 plays a crucial role in protecting intestinal inflammation by limiting the purinergic signaling mediated through the P2Y 6 receptor in colonic epithelial cells. This may be a novel therapeutic approach for the treatment of IBD 180 …”
Section: P2y Receptors G‐coupled Protein Receptorsmentioning
confidence: 99%